Spatial continuity in a mixed ombrophilous forest with different size and shape of sample units - Roveda, Marcelo (2016)
Size and shape of sample units are fundamental for the observation of spatial continuity in native forests and important to characterize patterns structured in space by different scales. Therefore, the objective of this study was to identify the spatial continuity of number of trees and basal area, evaluating the influence of size and shape of sample units in a mixed ombrophilous forest in Paraná State, Brazil. An area of 25 hectares was divided in 50 m x 50 m and 25 m x 25 m square sample units, and also in 10 m x 50 m and 20m x 50m rectangular sample units. In these samples, the number of trees (n.ha-1) and the basal area (m².ha-1) were determined in each of them, with the possible spatial continuity analyzed by geostatistics analysis. The influence of size and shape of sample units on the spatial continuity structure was analyzed. Also, adjusted semivariograms were used to observe that the correlation between neighboring sample units for number of trees was stronger than for the basal area. However, due to the similarity of the semiovariograms, both sizes and shapes can be used to describe the spatial structure of number of trees, while the square sample units were more appropriate to describe basal area.